Sounds of a City: Podcasts and Public Humanities in Baltimore - King, Nicole (The Journal of Higher Education Outreach and Engagement, 2021)
"Sounds of a City: Podcasts and Public Humanities in Baltimore" reflects on the Baltimore Traces: Communities in Transition project, a collaborative teaching endeavor that began in 2015 to document changing Baltimore neighborhoods through student-produced media. The essay provides a definition of public humanities and a discussion of organic methodological innovations that evolved through the process of creating a series of student-produced podcasts focused on listening to a city in a specific moment. Sharing authority and deeply listening to both students and the diverse voices of a city led to the “on the street” interview methodology. Organic methods blending journalism with scholarship, push engaged research into new transdisciplinary territory that centers voices from the street within the university classroom.
Keywords: collaborative teaching; Sounds of a City Podcasts and Public Humanities in Baltimore; student-produced media; on the street interview; public humanities